War and Peace Journalism: Coverage of Syrian Conflict in International Press - Usama Iftikhar, Usama Iftikhar; Dr. Zubair Shafiq (Journal of Peace, Development and Communication, 2021)
The Syrian issue is one of the hottest topics discussed in the global community in the recent decade. This research work aims to explore how the international press portrayed the Syrian conflict in terms of 'peace' and 'war' journalism. Four newspapers of different stokehold countries that are directly involved in the matter are selected. Editorial pages of The New York Times of America, The Moscow Times of Russia, Tehran Times of Iran, and Khaleej Times of Arab States are chosen as a unit of analysis for the study. A sample of 918 stories is finalized for examination. The Content analysis methodology is applied, and five years’ time period is selected from March 15, 20ll to March 15, 2016. Findings showed that the Syrian issue is dominantly framed as war-oriented by the international media as compared to peace-journalism. Among war-indicators, a dichotomy is the most used approach, whereas in peace-indicators solution-oriented approach is the most repeated one.